Measuring Financial Capability : Questionnaires and Implementation Guidance for Low-, and Middle-Income Countries - Kempson, Elaine (World Bank, Washington, DC, 2013)
This manual is designed to provide guidance to institutions, researchers, and survey firms on how to measure financial capability in middle, and low income countries using a new survey instrument that was developed and tested, from start to finish, in middle- and low-income countries. This new survey was developed as part of a larger project financed by the Russia Financial Literacy and Education Trust Fund (RTF) and implemented by the World Bank that encompassed both measurement of financial capability and evaluation of financial literacy programs. The development of the new RTF Financial Capability Survey (FCS) was done in collaboration with a team of external experts and teams from a total of 12 low- and middle-income countries. The full description of how the survey was developed can be found in Kempson, Perotti, and Scott (2013) along with findings from the first wave of surveys that have been done. In this manual we briefly summarize reasons why the FCS might be of interest to a country, provide a detailed outline of the issues related to implementing the survey successfully, and demonstrate how to analyze the resulting data. The first chapter of the manual lays out the reasons why this survey could be of use to policy makers. Chapter two describes the FCS questionnaires and their goals and objectives. Topics related to fieldwork, or the implementation of the survey, are covered in chapter three. Guidance on how to analyze the survey is provided in chapter four. The survey instruments can be found in the appendixes of this manual, and related documents, interviewer and supervisor manuals, can be found on the Trust Fund website www.finlitedu.org.